Strategi Tata Kelola Komunikasi Krisis Humas Pemerintahan Kabupaten Kuningan Jawa Barat dalam Menghadapi Krisis - Fitri Permata Sari; Rah Utami Nugrahani (Universitas Ahmad Dahlan, 2019)
Crisis is something that can suddenly unnoticed. A Public Relations is required to be able to control that impact. Every Public Relations should make a plan in handling crisis, the planning referred as Crisis Management. Kuningan District Government has a planning strategy in handling the crisis. The problem of e-ID card is an external crisis that occurred in Kuningan. This research uses descriptive qualitative research method in order to give description about Crisis Communication Management conducted by Public Relations of Regional Government of Kuningan Regency in handling e-KTP crisis that happened in Kuningan. There are three stages in handling the crisis that is with pre-crisis planning, during crisis and post crisis. The result of this research is communications crisis management activities conducted by the Regional Government of Kuningan Regency has gone through three stages. The first stage is pre crisis, the existence of planning on what to do if the crisis occurs. Local Government of Kuningan Regency in handling e-KTP crisis, they are quick response in handling crisis and also transparent to society. The last thing done after the crisis is by providing guidance and input to the Ahmadiyah community and related Islamic organizations.